Mach number at outlet plane of a straight micro-tube. (December 2016) - Kawashima, D; Yamada, T; Hong, C; Asako, Y
The Mach number and pressure at the outlet plane of a straight micro-tube were investigated numerically for both laminar and turbulent flow cases. The numerical methodology is based on the arbitrary Lagrangian-Eulerian method. The LB1 turbulence model was used for the turbulent flow case. The compressible momentum and energy equations with the assumption of the ideal gas were solved. The computational domain is extended to the downstream region from the micro-tube outlet. The back pressure was given to the outside of the downstream region. The computations were performed for a tube whose diameter ranges from 50 to 500 μm. The average Mach number at the outlet plane of the choked flow depends on the tube diameter and ranges from 1.16 to 1.25. The flow characteristics of the under-expanded gas flow in a straight micro-tube were revealed.